Single versus multiple human-equivalent doses of C. parvum in mice: neutralization of the anti-metastatic effect. - Mitcheson, H. D. (Nature Publishing Group, 1980)
The murine dose of i.v. C. parvum (466 microgram) was compared with a single, low, human-equivalent dose of 70 microgram and with repeated weekly low doses. All treatments increased the antibody titre against C. parvum (CP). However, repeated doses stimulated a much higher titre than single doses. In all treated animals spleen weight peaked at 2 weeks and then fell. A single low dose caused a 3-fold increase, a single high dose or multiple low doses a 6-fold increase. Liver weight changes followed a similar pattern. Hepatosplenomegaly was prolonged by multiple doses. The effects of these treatments on Lewis tumour metastases were studied. A single high dose and a single low dose on the day of tumour implantation (Day 0) were equally effective at inhibiting pulmonary metastases. Repeated low doses starting on Day 0 were no more effective than a single dose. The effect of CP on survival after primary-tumour excision on Day 10 was observed. Low dose CP on Day 7 doubled the harmonic mean of survival time. Repeated doses were no more effective than a single dose. Low-dose prophylaxis up to 2 weeks before tumour significantly inhibited metastases. However, when repeated low-dose prophylaxis was combined with a single low dose on Day 0, the anti-metastatic effect was abrogated. This neutralization of the anti-metastatic effect of CP given on Day 0 was found to persist after a 13-week treatment-free interval. Possible mechanisms for this phenomenon are discussed.